Development of PARISPHERE as the particle-based numerical wave flume for coastal engineering problems. Issue 1 (2nd January 2019) - Tsuruta, Naoki; Gotoh, Hitoshi; Suzuki, Kojiro; Ikari, Hiroyuki; Shimosako, Kenichiro
ABSTRACT: The paper presents a new numerical wave flume packaged as PARISPHERE code based on the Incompressible Smoothed Particle Hydrodynamics (ISPH) method with an improved framework for enhancement of the numerical accuracy and stability. PARISPHERE includes a new pressure gradient model for more enhancement and a new coupling model with Discrete Element Method (DEM)-ISPH to achieve flexible application of the spatial resolution between the solid and liquid targets. In addition, the existing porous model and scour model are introduced into the framework. Its enhancement is shown by comparing with the existing schemes through benchmarks with targeting a standing wave test, a wave propagation test, a breaking wave test, a dam break problem with a porous media, a drafting, kissing, and tumbling (DKT) problem, a two-phase flow, and a scour process by an overflowing tsunami.